2015
DOI: 10.1007/s00592-014-0702-z
|View full text |Cite
|
Sign up to set email alerts
|

Excess mortality in Type 1 diabetes diagnosed in childhood and adolescence: a systematic review of population-based cohorts

Abstract: Excess mortality in childhood-/adolescent-diagnosed Type 1 diabetes is apparent across countries worldwide. Excesses were less marked in more recent studies and in countries with lower infant mortality and higher health expenditure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 27 publications
2
62
0
1
Order By: Relevance
“…Methods, study populations, length of follow-up, and mortality in the background population tend to differ across studies. A recent systematic review of excess mortality in type 1 diabetes diagnosed in childhood and adolescence found no relationship between a country's incidence of diabetes and SMRs [19]. The SMR in our cohort is very similar to that in a Finnish cohort of childhood-onset diabetes (SMR 3.6) [4].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Methods, study populations, length of follow-up, and mortality in the background population tend to differ across studies. A recent systematic review of excess mortality in type 1 diabetes diagnosed in childhood and adolescence found no relationship between a country's incidence of diabetes and SMRs [19]. The SMR in our cohort is very similar to that in a Finnish cohort of childhood-onset diabetes (SMR 3.6) [4].…”
Section: Discussionsupporting
confidence: 74%
“…However, studies differ in populations, diagnosis periods, duration of diabetes and age at diagnosis and this makes it difficult to directly compare studies with each other. Morgan et al showed that the excess mortality in type 1 diabetes diagnosed in childhood and adolescence was less marked in more recent studies and in countries with lower infant mortality and higher health expenditure, which suggests potential explanations for the differences [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found no relationship between mortality and socioeconomic status derived from postcode at diagnosis. In a systematic review including studies from many nations, there was no relationship between mortality and gross domestic product per head of population but a reduction in mortality with increased expenditure on healthcare 19. Higher mortality rates among individuals from lower socioeconomic background have been reported in Western Australia 9…”
Section: Discussionmentioning
confidence: 99%
“…Type 1 diabetes (T1DM) is consistently associated with increased mortality, though the excess risk may have recently decreased (1). Large differences in T1DM mortality are seen internationally, with in general a smaller excess mortality in Europe than in the U.S. (1).…”
Section: Introductionmentioning
confidence: 99%